Open Approach Implementation in Understanding the Concept of Flat Shape for Elementary Schools in Indonesia - Sopiani, Sridini (IJCAR: Indonesian Journal of Classroom Action Research, 2024)
This study explores the implementation of the open approach in teaching flat shapes to fourth-grade students in a public elementary school in Ciamis Regency, Indonesia. Using qualitative research, data were collected via classroom observations and question sheets, focusing on student engagement and comprehension before, during, and after the implementation. Results show significant improvement in understanding flat shapes, transitioning from rote memorization to deeper conceptual grasp. The study also highlighted increased student participation, collaboration, and problem-solving skills. Findings suggest the open approach effectively fosters a supportive and interactive learning environment, enhancing mathematical proficiency. The implications indicate that adopting the open approach can lead to better student outcomes in mathematical understanding and engagement, promoting a more effective learning experience.